الأحاديث التي وقفها الإمام النسائي في كتابه عمل اليوم والليلة: دراسة تطبيقية - العبيدي، محمد سعدي شفيق (كلية الإمام الأعظم, 2023)
تناولت في بحثي هذا الأحاديث التي وقفها الإمام النسائي (رحمه الله تعالى) في كتابه (عمل اليوم والليلة)، وبعد جمع الأحاديث قمت بتتبع طرقها من كتب السنة المطهرة ودراستها ثم بعد ذلك رجحت بين تلك الطرق وبينت الراجح منها وقد اقتضت طبيعة البحث أن تقسم الخطة على مقدمة، وسبعة مطالب، وخاتمة، ثم قائمة المصادر والمراجع. والحمد لله رب العالمين وصلى الله على سيدنا محمد وعلى آله وصحبه أجمعين. In my research, I dealt with the hadiths that Imam al-Nisa’i (may God Almighty have mercy on him) stopped in his book (Action of the Day and Night), and after collecting the hadiths, I followed their methods from the books of the pure Sunnah and studied them, then after that I weighed between those methods and indicated the most correct of them. The nature of the research required that the plan be divided An introduction, seven requirements, a conclusion, then a list of sources and references, and praise be to God, Lord of the worlds, and may God’s blessings be upon our master Muhammad and his family and companions.
Keywords: الأحاديث النبوية -- رواة الأحاديث -- الأحاديث الموقوفة